Profiles of Problematic Internet Use and Its Impact on Adolescents’ Health-Related Quality of Life - Machimbarrena, Juan Manuel; González-Cabrera, Joaquín; Ortega-Barón, Jessica; Beranuy-Fargues, Marta; Álvarez-Bardón, Aitor; Tejero, Blanca (International Journal of Environmental Research and Public Health, 2020)
The internet has been a breakthrough for adolescents in many ways, but its use can also become dysfunctional and problematic, leading to consequences for personal well-being. The main objective is to analyze profiles related to problematic internet use and its relationship with health-related quality of life (HRQoL). An analytical and cross-sectional study was carried out in a region of northern Spain. The sample comprised 12,285 participants. Sampling was random and representative. Mean age and standard deviation was 14.69 ± 1.73 (11–18 years). The Spanish versions of the Problematic and Generalized Internet Use Scale (GPIUS2) and of the Health-Related Quality of Life (KIDSCREEN-27) were used. Four profiles were detected (non-problematic use, mood regulator, problematic internet use, and severe problematic use). The prevalence of these last two profiles was 18.5% and 4.9%, respectively. Problematic internet use correlated negatively and significantly with HRQoL. The severe problematic use profile presented a significant decrease in all dimensions of HRQoL. Analyses were carried out to extract a cut-off point for GPIUS2 (52 points). The results and practical implications are discussed.
Keywords: problematic internet use; health-related quality of life; adolescent; cut-off point; internet addiction; Scopus; JCR